Comparison of Chemotherapy Combined With Chidamide Versus Chemotherapy in the Frontline Treatment for Peripheral T-Cell Lymphoma - Wang, Jinni; Su, Ning; Fang, Yu; Ma, Shuyun; Zhang, Yuchen; Cai, Jun; Zou, Qihua; Tian, Xiaopeng; Xia, Yi; Liu, Panpan; Li, Zhiming; Huang, He; et al. (Frontiers in Immunology, 2022)
Background Peripheral T-cell lymphoma (PTCL) is featured with a poor survival outcome. China has approved chidamide, an oral novel histone deacetylase inhibitor, for patients diagnosed with relapsed or refractory PTCL. Objective We compared the benefit of traditional chemotherapy alone and a combination of chidamide and traditional chemotherapy against newly diagnosed PTCL. Prognostic factors related to progression and survival in patients diagnosed with untreated PTCL were also investigated. Methods 104 patients with newly diagnosed PTCL were enrolled and divided into chemotherapy (ChT) group and chemotherapy combined with chidamide (ChT+C) group. Survival curves were plotted by the Kaplan-Meier method. Univariate and multivariate analysis were conducted with Log-rank test and Cox’s proportional hazard regression. Subgroup analysis and interaction tests were conducted to evaluate factors associated with prognostic differences between ChT and ChT+C groups. Results Compared with patients in ChT group, those in ChT+C group had superior progression-free survival (PFS) (p=0.047). However, there was no significantly statistical difference observed between the two groups in overall survival (OS) (p=0.212). High IPI scores have a negative relationship with survival. Multivariate analysis revealed that the type of frontline treatment regimen is an independent factor associated with PFS of PTCL patients (p=0.045). In the subgroup of patients with high international prognostic index scores (3-5), the HR value for PFS comparing ChT with ChT+C was 4.675. A test of interaction between IPI and treatment showed statistical significance (p = 0.037), implying that the benefits of ChT+C are higher for patients with high IPI scores. Conclusions In summary, the combination of ChT and chidamide may provide a promising prospect for patients with newly diagnosed PTCL.